HUBUNGAN BODY SHAMING DENGAN KEPERCAYAAN DIRI SISWA SMPN 22 KOTA JAMBI - Khopsah; Ninil Elfira; Muhammad Alridho Lubis (CV. ALIM'SPUBLISHING, 2026)
This study aims to determine the relationship between body shaming and students’ self-confidence at SMPN 22 Kota Jambi. This research used a quantitative approach with a correlational design. The population consisted of 508 students, with a sample of 224 students selected using simple random sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The results showed that the level of body shaming was in the low category (32.11%), while self-confidence was in the high category (63.86%). The Spearman correlation test indicated a negative and significant relationship (ρ = -0.282; p < 0.05), meaning that higher levels of body shaming are associated with lower self-confidence. These findings indicate that body shaming has a psychological impact on students, particularly in influencing their self-confidence in social interactions